Robust Video Data Hiding Using Forbidden Zone Data Hiding and Selective Embedding - K, Narmatha; Vadivel, R (International Journal of Computer Sciences and Engineering, 2022)
The steganography has been used for long time before. The main use for it was for military and government messages, nowadays; the approaches of steganography become widely used for many purposes. Anyway, the researchers provide and found out many approaches while others enhanced the methods and the approaches of the steganography in order to improve the steganographic applications.Nowadays, the steganography application for sharing secure message used the multimedia files as a cover carrier for the secure message, since that many approaches has been proposed to use different type of the covers to send the secure message. The aim of this project is to use the methods of steganography using the video file as a cover carrier. The steganography is the art of protecting the information through embedding data in medium carrier. The video based steganography can be used as one video file. The use of the video based steganography can be more eligible than other multimedia files. As a result, the video based steganography the advantages of using the video file as a cover carrier for steganography have been proposed. In this project Steganography and encryption are bothused to ensure data confidentiality. However, the main difference between them is that with encryption anybody can see that both parties are communicating in secret. Steganography hides the existence of a secret message and in the best case nobody can see that both parties are communicating in secret.